Inhibition of arginase modulates T-cell response in the tumor microenvironment of lung carcinoma. (1st January 2021) - Sosnowska, Anna; Chlebowska-Tuz, Justyna; Matryba, Pawel; Pilch, Zofia; Greig, Alan; Wolny, Artur; Grzywa, Tomasz M.; Rydzynska, Zuzanna; Sokolowska, Olga; Rygiel, Tomasz P.; Grzybowski, Marcin; Stanczak, Paulina; et al.
ABSTRACT: Immunotherapy has demonstrated significant activity in a broad range of cancer types, but still the majority of patients receiving it do not maintain durable therapeutic responses. Amino acid metabolism has been proposed to be involved in the regulation of immune response. Here, we investigated in detail the role of arginase 1 (Arg1) in the modulation of antitumor immune response against poorly immunogenic Lewis lung carcinoma. We observed that tumor progression is associated with an incremental increase in the number of Arg1 + myeloid cells that accumulate in the tumor microenvironment and cause systemic depletion of ʟ-arginine. In advanced tumors, the systemic concentrations of ʟ-arginine are decreased to levels that impair the proliferation of antigen-specific T-cells. Systemic or myeloid-specific Arg1 deletion improves antigen-induced proliferation of adoptively transferred T-cells and leads to inhibition of tumor growth. Arginase inhibitor was demonstrated to modestly inhibit tumor growth when used alone, and to potentiate antitumor effects of anti-PD-1 monoclonal antibodies and STING agonist. The effectiveness of the combination immunotherapy was insufficient to induce complete antitumor responses, but was significantly better than treatment with the checkpoint inhibitor alone. Together, these results indicate that arginase inhibition alone is of modest therapeutic benefit in poorly immunogenic tumors; however, in combination with other treatment strategies it may significantly improve survival outcomes.